Analisis Yuridis Cryptocurrrency Dalam Prespektif Hukum Surat Berharga Di Indonesia - Noor Eva Rahma; Hilda Yunita Sabrie (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2022)
Abstractâ€” Cryptocurrency as a digital product has grown significantly. Cryptocurrency as a digital currency has been accepted by the world community, with different implementations in each country. Indonesian law regulates cryptocurrency as a commodity product that can be traded on the Futures Exchange. As a commodity, cryptocurrency monitoring is carried out by BAPPEBTI (Commodity Futures Trading Supervisory Agency). The position of cryptocurrency as a commodity is unfortunate by some, who expect cryptocurrencies to be recognized as legal tender as is the case in some countries. Securities law regulates the elements that must be met in order for an object to be recognized as a means of payment. This is also supported by current practices, namely the level of significant fluctuations in cryptocurrencies and the absence of government intervention which makes the government unable to carry out its role as controller. This study aims to determine the position of cryptocurrency in the perspective of Indonesian law. This study uses a type of normative juridical research with a statutory approach and a conceptual approach. The results of the study note that until now cryptocurrency cannot be recognized as a means of payment and is recognized as a commodity.Â Keywords: cryptocurrencies, securities law, means of payment